Analysis of E-Commerce Logistic Service Quality on Customer Satisfaction, Loyalty, and Brand Image in Indonesia - Harlan, Fandy Bestario; Tarigan, Yulinda; Riadi, Sugeng; Sitompul, Agnes Manuella (International Review of Management and Marketing, 2024)
The life of modern Indonesian society today must be connected to technology, one of which is e-commerce. Businesses that cannot be separated from e-commerce are logistics services that act as intermediaries between sellers and end consumers. Shopee, one of Indonesia’s biggest and most developed e-commerce sites, has expanded its business line by opening Shopee Xpress logistics services. This analysis aimed to see how the quality of Shopee Xpress logistics services can affect the satisfaction, loyalty, and brand image of consumers or Shopee users in Indonesia. This study uses a quantitative approach, and data was obtained through the distribution of questionnaires to 206 samples of Shopee and Shopee Xpress users throughout Indonesia. SEM method is used in data analysis, and LISREL 8.8 software is used. From the 7 hypothetical paths analyzed, it was found that 6 hypotheses of the quality of logistics services have a positive and significant impact on satisfaction, loyalty, and brand image. However, the hypothesis of customer satisfaction with the quality of logistics services has impacted customer loyalty when using Shopee Xpress logistics services.